The Customer Contentment with Products and Services in Telecommunications Sector in the Slovak Republic - Anna Krizanova; Gabriela Masarova; Juraj Kolencik (Communications - Scientific letters of the University of Zilina, 2014)
Communication is very important for people. Means of communication are constantly increasing and new forms, and ways of communication are developing because of technological innovations. The paper is focused on a part of the marketing research of customers´ contentment and their preferences in order to determine their requirements and preferences in the field of mobile and data services of mobile operators. Results and conclusions of this paper should help mobile operators to identify customers´ needs and allow to customize their service offers. The level of competition in the selected market is relatively low, despite the fact that it is growing nowadays. The first part of the paper focuses on the theoretical basis of customer satisfaction in the telecommunications market and the second part on preferences survey and customers´ contentment in the market and its evaluation results.